Evaluation of Sutureless, Glueless, Flapless, Intrascleral Fixated Posterior Chamber Intraocular Lens in Children with Ectopia Lentis - Kannan NB; Piyush Kohli; Bhanu Pratap Singh Pangtey; Kim Ramasamy (Journal of Ophthalmology)
Aim. This paper aims at evaluating refractive outcome and complication profile of sutureless, glueless, flapless, intrascleral fixation of intraocular lens (SFIOL) in pediatric population. Methods. This retrospective study included patients ≤18 years of age who underwent SFIOL for ectopia lentis. Details obtained included preoperative uncorrected visual acuity (UCVA), cycloplegic refraction, and best-corrected visual acuity (BCVA); intraoperative complications; and postoperative UCVA, cycloplegic refraction, and BCVA and complications. Results. Median pre- and postoperative UCVA was logMAR 1.78 (Snellen 20/1200) and logMAR 0.30 (Snellen 20/40), respectively, (p<0.001). Median pre- and postoperative BCVA was logMAR 0.24 (Snellen 20/34) and logMAR 0.18 (Snellen 20/30), respectively. UCVA ≥20/60 was attained in 90% of eyes. BCVA ≥20/30 was attained in 85.0% of eyes. Most common early postoperative complications were hyphaema (10%), transient vitreous hemorrhage (2.5%), and ocular hypotony (2.5%). None of these developed any long-term sequelae. Only one case of subluxation of IOL was seen. No case of late endophthalmitis or retinal detachment was seen. Conclusion. Since refractive error induced is minimal, the procedure is suitable for IOL implantation in children, who are noncompliant with spectacles. The complication profile is similar to that reported in adults.